Germline genetic testing reveals pathogenic variants in uterine serous carcinoma patients - Katelyn Tondo-Steele; Kara J. Milliron; Jean H. Siedel; Shitanshu Uppal; Sofia D. Merajver; Karen McLean (Elsevier, 2024)
An increase in the risk of developing uterine serous carcinoma (USC) has been observed among BRCA1 and BRCA2 germline pathogenic variant carriers in the published literature. However, routine germline genetic testing is not currently incorporated into USC management guidelines. The primary objective of this study is to define the incidence of germline pathogenic variants identified through genetic counseling referrals for USC patients at our institution. A retrospective cohort study was performed of patients diagnosed with USC at a single institution over a seven-year interval. A total of 91 patients with uterine serous carcinoma were identified. Almost half of the patients were referred to genetic counseling, and just over half of referred patients (24/43, 56%) ultimately underwent germline genetic testing. Pathogenic variants were noted in 12.5% (3/24) of the patients who were tested. Pathogenic mutations were found in BRCA1, BRCA2, and MSH6. Variants of unknown significance (VUS) were seen in 16.6% (4/24) of patients. Based on our findings, we recommend integration of germline testing into the standard management of patients with USC.